The stars are dying [large type] - Peñaranda, Chloe C. (Thorndike Press large print high octane., 2024)
"Astraea knows she must escape the tyrannical king who holds her captive. This quest leads her to the Libertatem, a succession of trials in which human lands compete for safety from vampires. But Astraea's made a bargain with Nyte, the beautiful, deadly vampire who stalks her dreams and haunts her waking hours. He promises to keep her safe, but she knows she cannot trust him, even as she finds herself drawn into his embrace. Caught between Nyte and her own mysteries, Astraea must decide if winning the Libertatem for her kingdom is worth her life, or if protection and the answers to her past really are her strongest desires."--Back cover.